A constitutive numerical modelling of hybrid-based timber beams with partial composite action. (30th July 2018) - Tran, T-T.; Thi, V-D.; Khelifa, M.; Oudjene, M.; Rogaume, Y.
Highlights: A numerical methodology to simulate the flexural behaviour of the hybrid timber beams was developed. The model was implemented as an external subroutine in Abaqus FE software. Comparison between experimental and numerical results is given. Abstract: This work focuses on the development of a three dimensional constitutive model for timber to simulate the flexural behaviour of hybrid timber-steel and timber-concrete beams. This is motivated by the lack of dedicated non linear material behaviour laws for timber in the commercial finite element software by compared to the conventional materials such as concrete and steel. The flexural behaviour of hybrid timber beams is very complex because of the combination of the two different material behaviours and their nonlinar and partial compostion action. Numerical simulation of such behaviour requires an accurate description of the nonlinear material behaviour, in particular that of timber because of its anisotropic nature. A realistic description of the material nonlinearities and of the composite action between the different materials could aid considerably in achieving acceptable predictions. An incremental approach based on the strong coupling between orthotropic elasticity, anisotropic plasticity with mixed nonlinear isotropic hardening and an isotropic damage is used. The developed constitutive model for timber is implemented in Abaqus code using an external subroutine. The 3D FE model is calibrated and validated through comparison with experimental data reported in literature. The model is able to predict the nonlinear structural response of hybrid beams in terms of load-midspan deflection, and provides an acceptable accuracy.